1998
DOI: 10.1021/es970996m
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Fluid Velocity and Cell Concentration on the Transport of Motile and Nonmotile Bacteria in Porous Media

Abstract: The effect of fluid velocity on the transport of motile and nonmotile bacteria was studied in saturated soil columns using radiolabeled cells. According to colloid filtration theory, decreasing the bulk fluid velocity in a porous medium increases the number of collisions of passive colloids with particles and, therefore, should result in increased colloid retention in porous media. However, for motile cells, there was a variation in cell retention significantly different from that predicted by filtration theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
172
3
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(199 citation statements)
references
References 56 publications
23
172
3
1
Order By: Relevance
“…These studies analyze the initial attachment of bacteria in terms of either collision efficiency or fraction of cells retained or both. Effects of cell surface heterogeneity [Simoni et al, 1998] and motile/ nonmotile cells [Camesano and Logan, 1998] on cell attachment in column studies have been recently reported. Studies of microbial attachment in a two-dimensional (2-D) miniature sand-filled aquifer simulator [Shonnard et al, 1994] and a biofilter [Taylor et al, 1993] are reported.…”
Section: Prior Experimental Approachesmentioning
confidence: 99%
“…These studies analyze the initial attachment of bacteria in terms of either collision efficiency or fraction of cells retained or both. Effects of cell surface heterogeneity [Simoni et al, 1998] and motile/ nonmotile cells [Camesano and Logan, 1998] on cell attachment in column studies have been recently reported. Studies of microbial attachment in a two-dimensional (2-D) miniature sand-filled aquifer simulator [Shonnard et al, 1994] and a biofilter [Taylor et al, 1993] are reported.…”
Section: Prior Experimental Approachesmentioning
confidence: 99%
“…This indicated that mainly P. fluorescens cells, that were tightly attached to sand grains, may have contributed to degradation activity. Kinetics of bacterial sorption on soil particles seemed to depend on bacterial density in the water phase [6], cell motility [4] and [10], the size of soil particles [5] or on the flow velocity [9]. Hence, motile P. fluorescens cells, which have a high tendency for attachment on surfaces [24], [54], lost their motility after adsorption onto the sand grains or on already attached cells [12].…”
Section: Nutrient Consumption Cell Concentrations and Biofilm Formationmentioning
confidence: 99%
“…Ce modĂšle tient compte de la concentration bactĂ©rienne initiale introduite dans le sol, de la concentration bactĂ©rienne mesurĂ©e Ă  l'instant t dans le sol, de la porositĂ© de la couche de sol, du rayon du tuyau collecteur, de la distance parcourue par l'eau d'infiltration, du facteur d'efficacitĂ© du collecteur, du coefficient de filtration et de l'efficacitĂ© de collision, cette efficacitĂ© de collision exprimant le rapport entre la concentration initiale des microorganismes et leur concentration instantanĂ©e le long de la colonne de sol (CAMESANO et LOGAN, 1998). La rĂ©tention des bactĂ©ries par le sol contribue Ă  l'Ă©puration des eaux usĂ©es qui s'infiltrent avec leurs contenus fĂ©caux et non-fĂ©caux, en direction de l'aquifĂšre.…”
Section: Tableauunclassified